A shake and a surge: Assessing the possibility of an earthquake-triggered eruption at Steamboat Geyser - Reed, Mara; Barth, Anna; Taira, Taka’aki; Farrell, Jamie; Manga, Michael (Volcanica, 2024)
When and why earthquakes trigger volcano and geyser eruptions remains unclear. In September 2022, Steamboat Geyser in Yellowstone, USA erupted 8.25 hours after a local M3.9 earthquake—an improbable coincidence based on the geyser’s eruption intervals. We leverage monitoring data from the surrounding geyser basin to determine if the earthquake triggered this eruption. We calculate a peak ground velocity of 1.2 cm s−1, which is the largest ground motion in the area since Steamboat reactivated in March 2018 and exceeds a threshold associated with past earthquake-triggered geyser eruptions in Yellowstone. Despite no changes in other surface hydrothermal activity, we found abrupt, short-lived shifts in ambient seismic noise amplitude and relative seismic velocity in narrow frequency bands related to the subsurface hydrothermal system. Our analysis indicates that Steamboat’s eruption was likely earthquake-triggered. The hours-long delay suggests that dynamic strains from seismic waves altered subsurface permeability and flow which enabled eruption.